Role of naringin in the treatment of atherosclerosis - Lu, Yan; Li, De-Hong; Xu, Ji-Mei; Zhou, Sheng (Frontiers in Pharmacology, 2024)
Atherosclerosis (AS) is a major pathological basis of coronary heart disease. However, the currently available medications are unable to effectively reduce the incidence of cardiovascular events in the majority of patients with AS. Therefore, naringin has been attracting considerable attention owing to its anti-AS effects. Naringin can inhibit the growth, proliferation, invasion, and migration of vascular smooth muscle cells, ameliorate endothelial cell inflammation and apoptosis, lower blood pressure, halt the cell cycle at the G1 phase, and impede growth via its antioxidant and free radical scavenging effects. These activities suggest the potential anti-AS effects of naringin. In this review article, we comprehensively summarized the latest findings on the anti-AS effects of naringin and their underlying mechanisms, providing a crucial reference for future research on the anti-AS potential of this agent.